2015
DOI: 10.21608/scvmj.2015.65027
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Serum Cortisol Level During Pregnancy in Ewes and The Effect of Fetal Number

Abstract: This study was carried out to monitor serum cortisol level in pregnant ewes and comparing it with the non-pregnant values. Also, cortisol levels were monitored in single-fetus bearing and twin-fetus bearing ewes. This study was carried out during the breeding season on 31 pregnant and 5 non-pregnant ewes. Pregnancy and fetal numbers were determined through transrectal ultrasonography. Blood samples were collected every two weeks starting at day 30 of pregnancy until day 135 of pregnancy. Blood samples were col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Thus, by stimulating PGF2α release, the level of oxytocin which provides myometrial contractions increases (Nagel et al, 2019). Some studies are reported that there were no significant differences in serum cortisol levels in the prepartum period between single and twin pregnant ewes (Medan et al, 2015) before and after pregnancy (Brunet and Sebastian, 1991) in ewes. Drost et al (1973) found that serum cortisol levels of parturition higher than the levels of prepartum period in ewes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, by stimulating PGF2α release, the level of oxytocin which provides myometrial contractions increases (Nagel et al, 2019). Some studies are reported that there were no significant differences in serum cortisol levels in the prepartum period between single and twin pregnant ewes (Medan et al, 2015) before and after pregnancy (Brunet and Sebastian, 1991) in ewes. Drost et al (1973) found that serum cortisol levels of parturition higher than the levels of prepartum period in ewes.…”
Section: Discussionmentioning
confidence: 99%
“…Lambs gain approximately 70 % of their birth weight in the last 6 weeks of pregnancy (Siggurdson, 1988). Pregnancy can cause physiological stress that increases maternal plasma cortisol (Keller-Wood, 1996;Medan et al, 2015). Cortisol is a glucocorticoid hormone that produced by the adrenal cortex in response to stress (Medan et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The maternal HPA axis adapts during pregnancy and regulate stress-related deleterious effects on the mother and offspring [70,71]. A non-diabetic pregnancy is a state of hyperactivity of HPA axis and of hypercortisolism especially towards late gestation [72][73][74][75]. The increased cortisol in late gestation is regulated by the placenta, an important source of secreting corticotropin-releasing hormone (CRH), which further enters the maternal pituitary gland via the hypophyseal portal circulation and enhances adrenocorticotropin (ACTH) synthesis and secretion into the peripheral circulation.…”
Section: Role Of Maternal Hypothalamic-pituitary-adrenal (Hpa) Axis I...mentioning
confidence: 99%